Pembangunan Lingkungan Ramah Anak Terkait Pemenuhan Hak Anak Pada Masa Pandemi di Kampung Leles, Condongcatur, Depok, Sleman, DIY - Ratna Junyekawati Sholikah; Subaidi Subaidi (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
This study aims to explore related to the fulfillment of children's rights through child-friendly villages both before and during the Covid-19 pandemic. The issue of violence against children is the main thing that must be addressed. Especially during the Covid-19 pandemic, complaints of violations of children's rights are increasing. Fulfilling the needs of children's rights is one of the obligations that must be carried out by the government, parents, and the community. Every child has the right to protection, especially from the family to the community. For this reason, the development of a child-friendly environment is one of the efforts to fulfill children's rights. This study used a qualitative method with interview techniques to the PPA Task Force. In addition, using literature studies related to previous research related to the research theme. The focus of this research is on the object of a child-friendly village related to the fulfillment of children's rights in one of the Child-Friendly Villages in Sleman Regency. The results of this study through Child Friendly Villages play an active role in facilitating child-friendly activities, especially during the Covid-19 pandemic. These facilities include activities carried out including dancing, playing with children in the provided playground, English language assistance and information and communication technology. In addition, there are also online group facilities to communicate or share related to children's problems, especially during this pandemic. This is so that they can help each other and provide solutions to each other. Thus, synergy is the main thing in Child Friendly Villages between Community-Based Integrated Child Protection (PATBM), PPA Task Force, RW, village officials, and the surrounding community.